1979
DOI: 10.1111/j.1471-0528.1979.tb10698.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Menopausal Status and Sequential Mestranol and Norethisterone on Serum Cholesterol, Triglyceride and Electrophoretic Lipoprotein Patterns

Abstract: SummaryThe serum cholesterol, trigylcerides and electrophoretic lipoprotein patterns of 35 postmenopausal women, who subsequently received sequential mestranol and norethisterone, were compared with those of 35 premenopausal women of the same age and weight. The postmenopausal women had a significantly higher level of serum cholesterol (p <0.01) than the premenopausal women, and a significant reduction (p <0.001) occurred in this group after two months of therapy. There was no significant difference in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…The reduction in serum cholesterol with graded sequential mestranol and norethisterone has already been reported (Magnani and Moore, 1976). In the present series there was a + Z l significant reduction in serum cholesterol concentration at all durations of therapy and these reduced levels were similar to those found in age-matched premenopausal women (Paterson et al, 1979). Although there were differences in mean serum cholesterol concentration at the different durations of therapy, these differences did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 74%
“…The reduction in serum cholesterol with graded sequential mestranol and norethisterone has already been reported (Magnani and Moore, 1976). In the present series there was a + Z l significant reduction in serum cholesterol concentration at all durations of therapy and these reduced levels were similar to those found in age-matched premenopausal women (Paterson et al, 1979). Although there were differences in mean serum cholesterol concentration at the different durations of therapy, these differences did not achieve statistical significance.…”
Section: Discussionsupporting
confidence: 74%
“…The present study revealed significant differences between the premenopausal untrained group and the postmenopausal untrained group in measures of Tc, LDL-C, HDL-C, HDL/Tc (P < 0.05) and no significance with regard to HDL-C (F> 0.05) ( Table 3). These findings support the notion that menopause adversely alters cholesterol lipid profiles by elevating LDL-C levels since HDL-C levels were not significantly affected by menopause (10,20,29). The present authors hypothesize that this change may predispose postmenopausal women to higher risk for CAD.…”
Section: Discussionsupporting
confidence: 88%
“…Menopause appears to be related to increased heart attack risk (20). Although no cause and effect has yet been established, studies suggest that changes in HDL-C, LDL-C, and Tc that accompany menopause may be responsible for the increased risk (6,9,10,20,29,34). The present study revealed significant differences between the premenopausal untrained group and the postmenopausal untrained group in measures of Tc, LDL-C, HDL-C, HDL/Tc (P < 0.05) and no significance with regard to HDL-C (F> 0.05) ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Over lapping results have been obtained during investigations on the long-term influence of estrogen withdrawal, either physiological (menopause) or therapeutic (postoophorecto my) on lipid metabolism [7,8); in these con ditions, triglycerides are usually unchanged, while cholesterol increases well above nor mal mean values.…”
Section: Introductionmentioning
confidence: 99%